The Use of Web GIS in The Rapid Evaluation Process of The Post-Earthquake Urban Building Stock - Kaya, Aşır Yüksel (Ankara University, 2023)
Map Application Programming Interfaces and Geographical Information Systems have been actively used to manage direct and analyze after-crisis spatial data. The use of GIS and cloud-based technologies has made spatial data analysis easier. Additionally, GIS and its components were increasingly used instead of conventional methods for damage assessment. The main purpose of the research is to exhibit the utility of web GIS software on damage assessments in the city after the 24 January 2020 Elazig Earthquake. The utility of web maps has been exhibited particularly in terms of collection, analysis, and access of end-user. In this particular research, ArcGIS software and web service have been used. The research has three phases: creating a database, uploading to web services, and creating web maps. Additionally, the building attribute data has been collected from onsite measurements to create a database, which is used in a rapid evaluation method for the detection of risky buildings in Elazig. Building attribute data collection and results of rapid evaluation method have been achieved as outcomes of the project called ‘The Creation of the information bank framework to Influence Urban Transformation and Earthquake Risk Maps for the Center Neighborhoods of the Elazig City’ project. In the last part, Elazig Building Information and Management System (EBİS), based on ArcGIS Online and ArcGIS Enterprise, was created with the base of GIS. As result, the structural condition of the buildings examined and how the buildings will perform under a probable destructive earthquake. © 2023, Ankara University. All rights reserved.
Keywords: Damage Determination; Disaster Management; Geographical Information Systems; Rapid Evaluation; Risk Evaluation; Urban Geography